KETERAMPILAN BERPIKIR TINGKAT TINGGI DALAM KEANTIAJAIBAN SUPER TOTAL SELIMUT GRAF CIRCULANT - Dewy, Elitta P; Dafik, Dafik; Setiawani, Susi (Kadikma, 2015)
Abstract. Cover total Labeling (a, d) -H- antimagical on a graph G = (V, E) is a bijectivefunction of the vertices and edges of a graph on the set of integers from 1, 2, 3, ...|V(G)|+|E(G)|, for every subgraph H of G which is isomorphic with H has a total labelingdifferent and form the arithmetic sequence. H-lebeling is said to have super antimagicalif vertices labeling and edge labeling where the label of vertices less than the label ofedges . One technique that can be applied to get a super anti-magic total labeling blanketon a graph that is engineering the partition of the set of integers with different sets d.Partition symbolized In this article examines the super labeling (a,d)-